Rediscovery of Diplazium procumbens (Athyriaceae) in Peninsular Malaysia after more than 70 years, with notes on the morphology, spore ornamentation and anatomy - Maideen, Haja; Aliah, Nur; Norhazrina, Nik; Go, Rusea (Phytotaxa, 2019)
Recent floristic sampling in Fraser’s Hill, Pahang, Malaysia resulted in recollection of a rare Diplazium species in Peninsular Malaysia, D. procumbens, a poorly known species which was first described by R.E. Holttum in 1940. In this paper, we provide comprehensive morphological and anatomical description of the species based on our thorough examination of specimens including the type, and designate a lectotype and isolectotype. We also studied the spore ornamentation of D. procumbens using scanning electron microscopy (SEM) and discovered that the spores have folds and non-fenestrate perine. Descriptions of the habitat and ecology are also presented.